Carillion: the failure that rocked the accounting profession - Smith, Susan (Henry Stewart Talks, 2020)
Financial analysis, risk analysis, Debt & unfunded pension liability, Contract estimates, Ratio and profit analysis, ROCE (return on capital employed)